232. Implementation of an edited-PRESS sequence for the detection of the 2-Hydroxyglutarate metabolite. (December 2018) - Savini, A.; Bianchini, D.; Belli, M.L.; Mezzenga, E.; Feliciani, G.; Ravaglia, V.; Falaschi, D.; Barone, D.; Cenni, P.; Sarnelli, A.
Abstract : Purpose: The 2-Hydroxyglutarate (2-HG) metabolite can be quantified with MR-spectroscopy using an edited-PRESS sequence with shifted echo times. This metabolite has a key role in staging low-grade gliomas. The aim of this work was to implement the edited-PRESS for the detection of the 2-HG within our MR-scanner. Furthermore, we studied several sequence parameters in order to optimize the spectrum signal-to-noise-ratio (SNR), while limiting the acquisition time. Methods: A homemade phantom containing a solution of choline (2 mM) and creatine (6 mM) was built to simulate the healthy brain tissue. A Philips Ingenia-3T scanner was used in service-mode to generate single-voxel MR-spectra using the edited-PRESS. The dependence of the SNR with the number of signal acquisitions (NSA) and the voxel volume was characterized. Furthermore, the impact of two shimming algorithms (automatic and semi-automatic) was studied. The LCModel software was used to fit the acquired spectra. The root-mean-square (RMS) between measured and fitted spectra was employed to evaluate the fit quality. Results: The SNR showed a linear correlation (R2 = 0.99) with the quantity [NSÂ(1/2) × Voxel Volume], which is consistent with the theoretical behaviour. In terms of spectrum SNR, a not significant difference (p = 0.38, paired t-test) was found between the shimming algorithms (Fig. 1). The fit RMS was inversely proportional (R2 = 0.99) to the quantity [NSÂ(1/2) × Voxel Volume]. A simple formula was derived from these results in order to calculate the optimum NSA, once the voxel volume has been fixed. Conclusions: The implemented PRESS generated MR-spectra whose SNR dependence was compatible with the theoretical behavior. Since the semi-automatic shimming algorithm did not improve the spectrum SNR significantly, the automatic modality is suggested. The developed formula can be used by the MR-technologists to rapidly determine the optimum NSA of the edited-PRESS, once the voxel volume has been fixed (Table 1 ).